Polyurethane Meniscal Scaffold: Does Preoperative Remnant Meniscal Extrusion Have an Influence on Postoperative Extrusion and Knee Function? - Gelber, Pablo E.; Torres-Claramunt, Raúl; Poggioli, Francesco; Pérez-Prieto, Daniel; Monllau, Joan C. (The Journal of Knee Surgery, 2020)
Meniscal extrusion (ME) has been identified as a risk factor in the development of knee osteoarthritis. The relevance of this finding when a meniscal scaffold is used has not been extensively studied. The objective of this study was to determine whether preoperative meniscal remnant extrusion (MRE) was correlated with postoperative scaffold extrusion (SE) or with functional outcomes at the 2-year follow-up. Retrospective study included all polyurethane scaffolds implanted with a minimum 2-year follow-up. A magnetic resonance imaging (MRI) was performed preoperatively and postoperatively at 2 years. Extrusion was measured in millimeters in a coronal view. Patients were assigned to either group 1 or 2 depending on the preoperative MRE being either <3 mm (minor extrusion) or 3 mm (major extrusion). Functional outcomes were analyzed by means of the Western Ontario Meniscal Evaluation Tool (WOMET), International Knee Documentation Committee, Kujala and Tegner scores, as well as visual analog scale. Satisfaction was also documented. Sixty-two out of 98 patients were available to undergo an MRI at final follow-up. The mean age was 41.3 years (range, 17–58) and the mean follow-up was 45 months (range, 25–69). The mean preoperative MRE was 2.8 mm (standard deviation [SD] 1.2) and the mean postoperative SE was 3.8 mm (SD 1.8) (p < 0.01). All functional scores improved during the study period. When the correlation (Spearman's rho) between the difference in extrusion between the pre 26 and postoperative periods and their correlation with the different scores was assessed, correlation was only observed in the WOMET (rho 0.61, p = 0.02). The preoperative MRE in Group 1 was 1.85 mm (SD 0.83) and 3.7 mm (SD 2.2) in Group 2 (p < 0.01). At final follow-up, SE was 3.86 mm (SD 0.7) in Group 1, whereas it was 3.98 mm (SD 1) in Group 2 (p = 0.81). No differences were observed in the scores used for these two groups. The SE observed at the 2-year follow-up after the implantation of a polyurethane scaffold did not depend on preoperative MRE (major or minor extrusion). The WOMET score, which was the only meniscal-specific functional scored used, showed some inferior results in the most extruded meniscal scaffolds. This is a retrospective case series. Level of evidence is 4.
Keywords: polyurethane scaffold; Actifit; meniscal extrusion; meniscus; knee